Driving without the brain? Effects of value predispositions, media attention, and science knowledge on public willingness to use driverless cars in Singapore - Ho, Shirley S. (2020)
This study employs the cognitive miser model and science literacy model as theoretical frameworks to investigate motivations behind public willingness to use driverless cars in Singapore. Findings from a large-scale survey of 1,006 adult Singaporeans indicate that public willingness to use driverless cars was strongly related to value predispositions, especially affect. Aside from having a direct relationship with willingness to use driverless cars, this study found that affect also had an indirect relationship with willingness to use driverless cars via benefit perceptions. Meanwhile, findings failed to reveal significant relationships between two types of science knowledge and willingness to use driverless cars. The findings shed light on the current public opinion on driverless cars in Singapore and lend support to the cognitive miser model over the scientific literacy model. Theoretical and practical implications are discussed.